Application of The Juridic-Scientific Religious Approach Model in Execution of Penal Law Enforcement - Anis Widyawati; Dian Latifiani; Nurul Fibrianti; Ridwan Arifin; Rohmat Rohmat (Universitas Negeri Semarang, 2022)
Reforming the criminal application legislation in the national legal system is critical. This research uses the paradigm of legal constructivism and the type of research used is juridical-sociological. Criminal law enforcement regulations are currently still scattered in various laws and regulations, it is not impossible that they will disrupt the law enforcement system, especially in the implementation of criminal decisions/actions. Character building is an effort to establish a conservation value system to achieve the value of justice, the value of certainty and the value of benefit in law enforcement for the implementation of criminal law. Therefore, efforts are needed to enforce the law on the implementation of criminal law through a juridical-scientific-religious approach that is oriented (guided) on â€œscienceâ€ (criminal implementation law) and â€œGodâ€™s guidanceâ€. The juridical-scientific religious approach is realized as a concrete effort to reform the law through reforming the substance and culture of the law. In reforming the legal substance, the religious approach is carried out by making religious teachings a source of motivation, inspiration, and creative evaluation source in building legal people with noble character, so that concrete efforts must be developed in the content of national legal development policies.